Clinical Application of Diagnostic Imaging of Chiari-Like Malformation and Syringomyelia - Rusbridge, Clare; Stringer, Felicity; Knowler, Susan P. (Frontiers in Veterinary Science, 2018)
Chiari-like malformation (CM) and syringomyelia (SM) is a frequent diagnosis in predisposed brachycephalic toy breeds since increased availability of MRI. However, the relevance of that MRI diagnosis has been questioned as CM, defined as identification of a cerebellar herniation, is ubiquitous in some breeds and SM can be asymptomatic. This article reviews the current knowledge of neuroanatomical changes in symptomatic CM and SM and diagnostic imaging modalities used for the clinical diagnosis of CM-pain or myelopathy related to SM. Although often compared to Chiari type I malformation in humans, canine CM-pain and SM is more comparable to complex craniosynostosis syndromes (i.e. premature fusion of multiple skull sutures) characterized by a short skull (cranial) base, rostrotentorial crowding with rostral forebrain flattening, small and ventrally orientated olfactory bulbs, displacement of the neural tissue to give increased height of the cranium and further reduction of the functional caudotentorial space with hindbrain herniation. MRI may further reveal changes suggesting raised intracranial pressure such as loss of sulci definition in conjunction with ventriculomegaly. In addition to these brachycephalic changes, dogs with SM are more likely to have craniocervical junction abnormalities including rostral displacement of the axis and atlas with increased odontoid angulation causing craniospinal junction deformation and medulla oblongata elevation. Symptomatic SM is diagnosed on the basis of signs of myelopathy and presence of a large syrinx that is consistent with the neuro-localization. The imaging protocol should establish the longitudinal and transverse extent of the spinal cord involvement by the syrinx. Phantom scratching and cervicotorticollis are associated with large mid-cervical syringes that extend to the superficial dorsal horn. If the cause of CSF channel disruption and syringomyelia is not revealed by anatomical MRI then other imaging modalities may be appropriate with radiography or CT for any associated vertebral abnormalities.